Levonadifloxacin, a recently approved benzoquinolizine fluoroquinolone, exhibits potent in vitro activity against contemporary Staphylococcus aureus isolates and Bengal Bay clone isolates collected from a large Indian tertiary care hospital. (3rd May 2020) - Bakthavatchalam, Yamuna Devi; Shankar, Abirami; Muniyasamy, Rajeshwari; Peter, John Victor; Marcus, Zervos; Triplicane Dwarakanathan, Hariharan; Gunasekaran, Karthik; Iyadurai, Ramya; Veeraraghavan, Balaji
Abstract: Objectives: Levonadifloxacin (WCK 771; IV) and its prodrug alalevonadifloxacin (WCK 2349; oral) are benzoquinolizine fluoroquinolones, recently approved in India for the treatment of acute bacterial skin and skin structure infections with concurrent bacteraemia and diabetic foot infections. Ahead of its market launch, the present study aimed to assess the in vitro activity of levonadifloxacin against contemporary Staphylococcus aureus isolates collected from a large tertiary care hospital in India. Additionally, levonadifloxacin activity was tested against hVISA and Bengal Bay clone MRSA isolates. Methods: Non-duplicate S. aureus ( n = 793) isolates collected at Christian Medical College hospital, Vellore, India during 2013–19 were included in the study. MRSA isolates were identified using a cefoxitin disc diffusion assay. MICs of levonadifloxacin and comparator antibiotics were determined using the broth microdilution method. Mutations in QRDRs were identified for selected levofloxacin-non-susceptible isolates. MLST profiling was undertaken to detect the Bengal Bay clone. Results: Among the 793 isolates, 441 (55.6%) were MRSA and 626 (78.9%) were non-susceptible to levofloxacin. Levonadifloxacin showed MIC50 and MIC90 values of 0.25 and 0.5 mg/L, respectively, for all S. aureus, which included hVISA and Bengal Bay clone MRSA. The potency of levonadifloxacin was 16 times superior compared with levofloxacin. Conclusions: The present study demonstrated potent activity of levonadifloxacin against contemporary S. aureus isolates, which included MRSA isolates, hVISA isolates, Bengal Bay clone isolates and a high proportion of quinolone-non-susceptible isolates. The potent activity of levonadifloxacin observed in this study supports its clinical use for the treatment of S. aureus infections.